A comprehensive picture of foraging strategies of Neoseiulus cucumeris and Amblyseius swirskii on western flower thrips. Issue 12 (9th August 2021) - Dalir, Sajjad; Hajiqanbar, Hamidreza; Fathipour, Yaghoub; Khanamani, Mostafa
Abstract: BACKGROUND: This study evaluated the potential of Neoseiulus cucumeris Oudemans and Amblyseius swirskii Athias‐Henriot (Acari: Phytoseiidae) for controlling western flower thrips (WFT), Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), by determining the functional response, numerical response, prey switching and mutual interference behaviors of the predators. RESULTS: A type II functional response was detected for two predator species fed on WFT first instars. The attack rate was higher for A. swirskii than N. cucumeris, but the handling time of N. cucumeris was shorter. For two predator species, numerical response was affected by both prey density and oviposition time. The per capita searching efficiencies of the two predators decreased significantly with increasing predator densities. The interference coefficient for A. swirskii was less than that of N. cucumeris . Although N. cucumeris switched from feeding on WFT first instars to feeding on second instars, this behavior was not observed in A. swirskii . CONCLUSIONS: Comparison of the two predator species foraging behaviors indicated optimal performance by A. swirskii at lower F. occidentalis densities. N. cucumeris was found to perform optimally at relatively higher prey densities. Moreover, N. cucumeris could be more effective in stabilizing the predator–prey system by switching behavior compared with A. swirskii . At higher predator densities, A. swirskii seemed to be an effective agent owing to its reduced intraspecific competition compared with N. cucumeris . Findings from this study will be useful in selecting appropriate agents and developing effective biocontrol programs to control WFT. © 2021 Society of Chemical Industry. Abstract : The foraging behaviors of two predator species indicated optimal performance by Amblyseius swirskii at lower Frankliniella occidentalis densities. Neoseiulus cucumeris was determined to perform optimally at relatively higher prey densities. Moreover, N. cucumeris could be more effective in stabilizing the predator–prey system by switching behavior.